2012
DOI: 10.4028/www.scientific.net/msf.727-728.826
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Influence of the Silane Drying Temperature on the Feldspar and Zirconia-Based Ceramics Surfaces

Abstract: Ceramics are widespread used in restorative dentistry, mainly due to their aesthetics features. However, adequante bond strenght of this type on restoration to tooth structure spawned several investigations which aim to develop a clinical protocol for ceramic surface treatment. The objective of this study was to evaluate the influence of air temperature on the drying process of silane agent and the adhesion of feldspar and yttrium stabilized zirconia. They were divided into three groups (n=10): control; room t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
5
1
Order By: Relevance
“…Alternative methods to enhance the adhesion of zirconia include aluminum oxide gushing and silica tribochemical coating [105]. The latest technique is warm air which did not match with the findings of this meta-analysis as no improvement in the bond strength was observed [49].…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Alternative methods to enhance the adhesion of zirconia include aluminum oxide gushing and silica tribochemical coating [105]. The latest technique is warm air which did not match with the findings of this meta-analysis as no improvement in the bond strength was observed [49].…”
Section: Discussioncontrasting
confidence: 56%
“…After reading the full text, nine articles were excluded due to several reasons: in (4), the bond strength was not evaluated [18,[30][31][32]; in (4), a warm air stream was not tested [33][34][35][36]; and (1) was a thesis [37]. Then, a total of 28 articles were included in the qualitative analysis [12][13][14]16,20,21,23,24,29,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]. One study was excluded from the meta-analysis because there were no more studies for comparison [53].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figures 1 to 10 show morphology of the surface of the samples of each group. A qualitative morphological analysis showed that hydrofluoric acid, at the concentrations and the proposed experimental times, was able to dissolve the glassy matrix of the ceramic lithium disilicate, exposing the crystals and promoting an irregular surface, improving micromechanical retention between the ceramic and the cementing agent [5,7,8,13,14,15].…”
Section: Morphological Analysismentioning
confidence: 99%
“…However, the prosthetic tooth preparation, the prior dental substrate conditioning and the treatment of the ceramic surface directly influence the retention and longevity of an indirect restoration. Therefore, the success of ceramic restorations is dependent on the bond between resin cement, dental substrate and restore [3,4,5].…”
Section: Introductionmentioning
confidence: 99%